Recent Innovative Solutions in Eddy Current Non-Destructive Diagnosis - Ladislav Janousek; Milan Smetana; Mihai Iulian Rebican; Tatiana Strapacova; Anton Duca; Viera Pernisova (Communications - Scientific letters of the University of Zilina, 2013)
Recent innovative solutions in eddy current non-destructive evaluation of conductive materials are reported in the paper. Two main areas influencing reliability and preciseness of real cracks diagnosis are discussed. Advances in sensor technology are concerned at first. Innovative sensor design allowing sensing all the three spatial components of the perturbation electromagnetic field is presented. A novel approach for automatic diagnosis of real cracks from two-dimensional eddy current response signals is then introduced. The tabu search is applied for the three-dimensional reconstruction of partially conductive cracks.